An Analysis of Gender Gap in Access to Extension Services - Deka, Manoshi Baruah; Saikia, Pompi; Saikia, Rekha Moni (Indian Journal of Extension Education, 2018)
Women produce between 60 -80 percent of food in most developing countries and are responsible for half of the world's  food production with fewer resources, less access to technology and the added responsibility of child and family but they  receive little or no support from mainstream agricultural extension services. This paper reports information on gender  differentials in access to extension services in the state of Assam . Using a cross-sectional study design, data was collected  from a random sample of 1100 farm families. In majority (53.20 %) of the households, men owned land compared to 31.5  per cent and 15.3 per cent that was either jointly owned or by women. Both rural women and men included as respondents  in the present study possessed knowledge of different extension personnel, Access to extension information was  dominated by 47.5 per cent of the men while only 32.5 per cent of the women had access. Reasons given for non  participation was that the shortage of time for both rural women and men (58.23 %) ,sometimes it was because organising  without prior notice (48.11 %) and also venue and time not suitable to participate. However, there is a gender bias on the  part of the institutions providing extension services. Findings show that despite the women's important role in agricultural  production, disparities exist in the receiving extension services and training programmes in the province. Factors shaping  the gender gap were found to be due to notions about who is a farmer and narrow definition of women's roles in  agriculture, targeting rural women as extension clients and targeting male extension agents. It is strongly recommended to  train men extension agents in culturally acceptable methods of delivering extension services to women along with  alternate extension methodologies such as ICTs.
Keywords: Extension agents; extension services; gender; ICT; knowledge; problems